DOSAGE COMPENSATION: REGULATION OF SEX CHROMOSOME GENE EXPRESSION - E. V. Dementyeva (Вавиловский журнал генетики и селекции)
Dosage compensation is observed in various taxa of organisms with heteromorphic sex chromosomes. Dosage compensation mechanisms are thought to have arisen to eliminate differences in gene dosage between sexes that appeared in the course of sex chromosome evolution. Study of this process in the sex chromosomes of Drosophila melanogaster, Caenorhabditis elegans, and mammals has shown that, despite the common reason of dosage compensation origin, entirely different ways were elaborated to regulate X-linked gene expression level. It has also been found that not only equal levels of X-linked gene expression between sexes but also the transcription balance between the X chromosome and autosomes is important. Detailed examination of dosage compensation mechanisms demonstrates that X-linked genes are differently involved in the dosage compensation system. A similar trend is observed in studies of dosage compensation of Z-linked genes in birds and butterflies. Current data on the dosage compensation process and mechanisms governing it are summarized.